Efficiency of biological control against citrus whiteflies in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Three harmful citrus-feeding whiteflies reached Italy during the last twenty-five years; they all have been efficiently controlled through biological methods and the serious problems deriving from their initial infestations were rapidly solved. In particular, Dialeurodes citri (Ashmead), which invaded the Italian citrus orchards starting from the early sixties, has been pushed under low population levels by the introduction of Encarsia lahorensis (Howard); thus the whitefly only occasionally infests at present citrus groves, as a consequence of the relevant parasitization (up to 70-80%) by the Aphelinid. Two species of parasitoids have been more recently released for biological control of the Woolly Whitefly, Aleurothrixus floccosus (Maskell), which massively spread in Italy at beginning of the eighties; one of them, Cales noacki Howard, well established itself in the new agrosystems, performing, in lack of limiting factors (i.e. high temperatures and low relative humidity), a generally appreciable control of the whitefly, in spite of the frequent late summer outbreaks of the latter. Recently, at last, appreciable activity has been locally shown by Encarsia meritoria Gahan against the latest whitefly arrived in Italy, Parabemisia myricae (Kuwana); yet the most successful results in controlling this insect have been obtained through the introduction from Israel of Eretmocerus debachi Rose & Rosen, which allowed a quick reduction in the infestation levels by the whitefly.
Keywords: citrus whiteflies; biological control; Italy